Disease incidence of Monilinia fructigena coupled with codling moth damage and mechanical injury in an organic apple orchard - Holb, I. J. (International Journal of Horticultural Science, 2013)
In a two-year-study, disease incidence of Monilinia fructigena were quatified and the importance of certain fruit wounding agents was determined. The first infected fruits were observed at the beginning of August in 2011 and 2012. Disease development was continuous until fruit harvest in both years. Pre-harvest yield loss caused by M. fructigena amounted on average 26.3% in 2011 and 40.4% in 2012 by fruit harvest. All infected fruits were injured mainly by mechanical injury factors and codling moth (Cydia pomonella). In this study, the most important wounding agents were codling moth and mechanical injury factors in organic apple orchards. In both years, our results showed that 65-75% of the infected fruits were damaged by codling moth in organic apple production. Moreover, 5-15% of the infected fruits were mechanically injured in the two years. Our results indicated that most of the damaged fruits fell on the orchard floor before harvest and they became an important secondary inoculum source of M. fructigena. Biological and practical implications of the results are discussed.